1994
DOI: 10.1002/jmv.1890430216
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus subtypes and hepatitis C virus genotypes in patients with chronic liver disease or on maintenance hemodialysis in Indonesia

Abstract: Hepatitis B surface antigen (HBsAg) and hepatitis C virus (HCV) RNA were surveyed in patients in Yogyakarta, Indonesia, and their subtypes and genotypes were determined by serological methods and polymerase chain reaction with type-specific primers, respectively. Of 149 patients with chronic liver disease including 24 with chronic hepatitis, 86 with liver cirrhosis, and 39 with primary hepatocellular carcinoma, HBsAg was detected in 40 (27%) and HCV RNA in 48 (32%); one patient was positive both for HBsAg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
(15 reference statements)
5
13
0
Order By: Relevance
“…Our own sequence analysis of a subset of the Thailand blood donor samples in the core and NS-5 regions has revealed the existence of several new subtypes of type 3 (L. M. Jarvis and others, unpublished information) distinct from the six described from Nepal (Tokita et al, 1994). However, this more detailed analysis has confirmed that type 3a followed by 3b are the commonest subtypes in Thailand.…”
Section: Far-east and South-east Asiamentioning
confidence: 78%
See 3 more Smart Citations
“…Our own sequence analysis of a subset of the Thailand blood donor samples in the core and NS-5 regions has revealed the existence of several new subtypes of type 3 (L. M. Jarvis and others, unpublished information) distinct from the six described from Nepal (Tokita et al, 1994). However, this more detailed analysis has confirmed that type 3a followed by 3b are the commonest subtypes in Thailand.…”
Section: Far-east and South-east Asiamentioning
confidence: 78%
“…Few 5'NCR sequences are available for type 3 subtypes other than type 3a (Tokita et al, 1994). All 16 type 3a 5'NCR sequences have a C to U substitution at position -164 and a G to A substitution at position -121 (Simmonds et al, 1994b;Tokita et al, 1994) destroying ScrFI restriction sites.…”
Section: Predicted Electropherotypes Of Published Hc V 5"ncr Sequencementioning
confidence: 99%
See 2 more Smart Citations
“…In developing countries, the cause of 25-55% of LC and 42-46% of cases of HCC is unknown [45][46][47][48][49][50]. High incidence of HVD in Nepal and reports of 2,677 cases of IVCO from four hospitals in China during the period 1981-2003 [51] suggested that HVD is still an important cause of HVOO in developing countries.…”
Section: Pathogenesis Of Lc/hcc In Hvdmentioning
confidence: 99%